Utilization of primary tumor samples for cancer neoantigen discovery - Yong Li; Steven A Rosenberg; Paul Robbins; Billel Gasmi; Todd D Prickett; Jared J Gartner; Devikala Gurusamy; Stephanie L Goff; Vid Leko; Victoria Hill; Frank J Lowery; Bradley Sinclair White; et al. (Journal for ImmunoTherapy of Cancer)
Background The use of tumor-infiltrating T lymphocytes (TIL) that recognize cancer neoantigens has led to lasting remissions in metastatic melanoma and certain cases of metastatic epithelial cancer. For the treatment of the latter, selecting cells for therapy typically involves laborious screening of TIL for recognition of autologous tumor-specific mutations, detected through next-generation sequencing of freshly resected metastatic tumors. Our study explored the feasibility of using archived formalin-fixed, paraffin-embedded (FFPE) primary tumor samples for cancer neoantigen discovery, to potentially expedite this process and reduce the need for resections normally required for tumor sequencing.Method Whole-exome sequencing was conducted on matched primary and metastatic colorectal cancer samples from 22 patients. The distribution of metastatic tumor mutations that were confirmed as neoantigens through cognate TIL screening was evaluated in the corresponding primary tumors. Mutations unique to primary tumors were screened for recognition by metastasis-derived TIL and circulating T lymphocytes.Results We found that 25 (65.8%) of the 38 validated neoantigens identified in metastatic tumors from 18 patients with colorectal cancer were also present in matched primary tumor samples. This included all 12 neoantigens encoded by putative cancer driver genes, which are generally regarded as superior targets for adoptive cell therapy. The detection rate for other neoantigens, representing mutations without an established role in cancer biology, was 50% (13/26). Gene products encoding neoantigens detected in the primary tumors were not more likely to be clonal or broadly distributed among the analyzed metastatic lesions compared with those undetected in the primary tumors. Additionally, we found that mutations detected only in primary tumor samples did not elicit recognition by metastatic tumor-derived TIL but could elicit specific recognition by the autologous circulating memory T cells.Conclusions Our findings indicate that primary FFPE tumor-derived screening libraries could be used to discover most neoantigens present in metastatic tumors requiring treatment. Furthermore, this approach can reveal additional neoantigens not present in resected metastatic tumors, prompting further research to understand their clinical relevance as potential therapeutic targets.